2002
DOI: 10.1088/0953-8984/14/34/317
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and structural properties of micro-and nanometre-sized crystalline copper monoxide ceramics investigated by positron annihilation

Abstract: Electronic and structural properties of copper monoxide (CuO) sintered as a common ceramic and nanoceramic are studied by positron annihilation spectroscopy. A CuO nanoceramic with crystallite size ranging from 15 to 90 nm was prepared from a common one by shock-wave loading. It is found that the momentum distribution of valence electrons in CuO is shifted, as compared with metallic copper, towards higher momentum values. This result is related to the effect of the Cu 3d–O 2p hybridization in the Cu–O ionic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The Fe-Ni-Ti alloy represented a supersaturated solid solution relative to titanium and underwent the radiation-induced decomposition at this irradiation temperature, which was accompanied by the formation of fine ($5 nm) particles of the Ni 3 Ti intermetallic [18]. It was shown [19] that coherent intermetallic particles retarded the accumulation of vacancy defects in austenitic alloys at the elevated irradiation temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe-Ni-Ti alloy represented a supersaturated solid solution relative to titanium and underwent the radiation-induced decomposition at this irradiation temperature, which was accompanied by the formation of fine ($5 nm) particles of the Ni 3 Ti intermetallic [18]. It was shown [19] that coherent intermetallic particles retarded the accumulation of vacancy defects in austenitic alloys at the elevated irradiation temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The PAS technique has been used previously for characterizing ceramics, [11][12][13][14][15] including zirconia. [16][17][18][19] The positron annihilation lifetime spectroscopy ͑PALS͒ mode has been the most commonly used, but the angular correlation of the annihilation radiation ͑ACAR͒ and Doppler broadening have been used as well.…”
Section: Introductionmentioning
confidence: 99%
“…In a study using ACAR measurements on CuO compacts, 14 it was reported that an increase in the low-momentum fraction annihilations ͑associated with an increase in the open-volume signal͒ seen in nanometric samples ͑15-90 nm͒ was attributed to positron trapping at grain boundaries. In another study on nanocrystalline SnO 2 compacts by Shek et al, 15 the average positron lifetime decreased with increasing sintering temperature, an observation attributed to the elimination of grain boundaries by grain growth during the sintering process.…”
Section: Introductionmentioning
confidence: 99%
“…The results of theoretical calculation and experiment in cuprate superconductors have proved that the dominant positron traps were presented by oxygen vacancy defects in the Cu-O planes [38][39][40] . It was also reported that open volumes which were mainly identified as anion vacancy defects existed in the grain interfaces in the CuO nanoceramics as well as the oxygen vacancy defects led to a decrease in the degree of Cu-O bond covalency studied by PAS 30 . Therefore, in present study, we consider that the effects of positron trapping at positively charged vacancies (V O ) cannot be neglected.…”
Section: / Cos =mentioning
confidence: 96%
“…Doppler broadening parameters give information about the electron momentum distribution at the annihilation site 27 . Some authors investigated defect structure of CuO nanoparticles by positron annihilation technology [28][29][30] . They found that there existed a large number of copper-and/or oxygen-related vacancies or complexes in CuO nanoparticles, which depended on the annealing environment and temperature.…”
Section: Introductionmentioning
confidence: 99%